A statistical interaction between circumsporozoite protein-specific T cell and antibody responses and risk of clinical malaria episodes following vaccination with RTS,S/AS01E. - Francis M Ndungu; Jedidah Mwacharo; Domtila Kimani; Oscar Kai; Philippe Moris; Erik Jongert; Johan Vekemans; Ally Olotu; Philip Bejon (PLoS ONE)
The candidate malaria vaccine RTS,S/AS01(E) provides significant but partial protection from clinical malaria. On in vitro circumsporozoite protein (CSP) peptide stimulation and intra-cellular cytokine staining of whole blood taken from 407 5-17 month-old children in a phase IIb trial of RTS,S/AS01(E), we identified significantly increased frequencies of two CSP-specific CD4+ T cells phenotypes among RTS,S/AS01(E) vaccinees (IFNγ-IL2+TNF- and IFNγ-IL2+TNF+ CD4+ T cells), and increased frequency of IFNγ-IL2-TNF+ CD4+ T cells after natural exposure. All these T cells phenotypes were individually associated with reductions in the risk of clinical malaria, but IFNγ-IL2-TNF+ CD4+ T cells independently predicted reduced risk of clinical malaria on multi-variable analysis (HR = 0.29, 95% confidence intervals 0.15-0.54, p<0.0005). Furthermore, there was a strongly significant synergistic interaction between CSP-specific IFNγ-IL2-TNF+ CD4+ T cells and anti-CSP antibodies in determining protection against clinical malaria (p = 0.002). Vaccination strategies that combine potent cellular and antibody responses may enhance protection against malaria.